Correction: Constitutive expression of an A-5 subgroup member in the DREB transcription factor subfamily from Ammopiptanthus mongolicus enhanced abiotic stress tolerance and anthocyanin accumulation in transgenic Arabidopsis. - Meiyan Ren; Zhilin Wang; Min Xue; Xuefeng Wang; Feng Zhang; Yu Zhang; Wenjun Zhang; Maoyan Wang (PLoS ONE)
[This corrects the article DOI: 10.1371/journal.pone.0224296.].